2021
DOI: 10.1073/pnas.2016289118
|View full text |Cite
|
Sign up to set email alerts
|

Noncanonical immune response to the inhibition of DNA methylation by Staufen1 via stabilization of endogenous retrovirus RNAs

Abstract: DNA-methyltransferase inhibitors (DNMTis), such as azacitidine and decitabine, are used clinically to treat myelodysplastic syndrome (MDS) and acute myeloid leukemia (AML). Decitabine activates the transcription of endogenous retroviruses (ERVs), which can induce immune response by acting as cellular double-stranded RNAs (dsRNAs). Yet, the posttranscriptional regulation of ERV dsRNAs remains uninvestigated. Here, we find that the viral mimicry and subsequent cell death in response to decitabine require the dsR… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(36 citation statements)
references
References 43 publications
0
36
0
Order By: Relevance
“…Elsewhere in mammalian genome, the silencing response induced by DNA methylation of ERV elements is reinforced by the KAP1/SETDB1/DNMT1 dependent H3K9 tri-methylation ( 32 , 33 ). In murine embryonic stem cells the H3K9me3 induced heterochromatinization seem to require the ATRX and DAXX-dependent deposition of histone H3.3, as H3.3 deletion decreases the H3K9me3 levels especially in correspondence to class I and class II ERVs ( 21 , 34 ). The incorporation of H3.3 by the histone chaperone Daxx requires a functional Morc3-ATPase cycle and Morc3-SUMOylation, as Morc3 knock-out leads to reduced H3.3 and H3K9me3 deposition and to the de-repression of ERVs ( 35 ).…”
Section: Regulation Of Erv Expression At Transcriptional and Post-tra...mentioning
confidence: 99%
“…Elsewhere in mammalian genome, the silencing response induced by DNA methylation of ERV elements is reinforced by the KAP1/SETDB1/DNMT1 dependent H3K9 tri-methylation ( 32 , 33 ). In murine embryonic stem cells the H3K9me3 induced heterochromatinization seem to require the ATRX and DAXX-dependent deposition of histone H3.3, as H3.3 deletion decreases the H3K9me3 levels especially in correspondence to class I and class II ERVs ( 21 , 34 ). The incorporation of H3.3 by the histone chaperone Daxx requires a functional Morc3-ATPase cycle and Morc3-SUMOylation, as Morc3 knock-out leads to reduced H3.3 and H3K9me3 deposition and to the de-repression of ERVs ( 35 ).…”
Section: Regulation Of Erv Expression At Transcriptional and Post-tra...mentioning
confidence: 99%
“…Concomitantly, STAU1, which contains multiple dsRBDs, has been shown to cooperate with a long non coding RNA, TINCR, to binds ERV transcripts. The STAU1-TINCR-ERV complex stabilizes ERV transcripts and is required to promote the expected immune response and cell death ( 337 ). Therefore, by mediating the efficiency of the DNMTis treatments, levels of STAU1 and TINCR are important indicators of patient receiving DNMTis treatment.…”
Section: Mrna Stabilitymentioning
confidence: 99%
“… 13 Post-transcriptionally, dsRNA-binding protein STAUFEN1 and long noncoding RNA TINCR form a complex to stabilize SINE and ERV RNAs activated by DAC to ensure downstream innate immune activation. 9 Notably, the patients with low expression of STAUFEN1 and TINCR showed inferior response to the HMA therapy. 9 In an effort to develop markers to predict the effectiveness of HMAs, a number of high-throughput studies characterized the demethylation by HMAs, 9 , 10 , 14 , 15 but we still do not fully understand the extent of dsRNA induction required for sufficient downstream effect of HMAs to take place.…”
Section: Introductionmentioning
confidence: 99%
“… 6 , 7 Recently, numerous studies have shown that demethylation by HMAs also results in the transcription of endogenous double-stranded RNAs (dsRNAs), including endogenous retrovirus (ERV), short-interspersed nuclear element (SINE), and long-interspersed nuclear element (LINE) RNAs. 8 , 9 , 10 , 11 , 12 These dsRNAs are recognized by dsRNA sensors of the innate immune response systems, such as protein kinase R (PKR) and melanoma differentiation-associated protein 5 (MDA5), which leads to global suppression of translation and induces apoptosis by transforming the cells into the viral mimicry state. 9 , 11 The strength of immune activation by HMAs is regulated at multiple levels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation